A Carência de acessibilidade nos logradouros públicos, mormente nas calçadas, do município de Belém/Pa - MELO, Thalys Augusto Nunes de (2021)
This paper deals with the implementation of the right to accessibility in public places of Belém/PA. Due to the observation of the difficulties faced by people with disabilities or reduced mobility when moving around the streets, avenues, squares and traffic islands of the city, it was verified the need for the making and publication of this research. Thus, initially, brief considerations were made about the right to accessibility, its fundamentals and its importance, so that, later on, the international, national and local laws that promote and protect the right to accessibility in public places could be listed and addressed, regarding especially on the sidewalks of the municipality. In order to verify the reality faced by people with disabilities or people with reduced mobility when moving around, photographs were captured in various parts of the city and questionnaires were delivered, thorugh a processo f field research. At the end of the work, it was verified the precarious condition of the public places of the Municipality of Belém, which demonstrates the non-implementation of public policies by the competent authorities, which lead to the adoption of judicial measures, listed during the work, against these same authorities. With this research, it is expected that the public agents responsible for enforcing the legislation regarding the guarantee of accessibility act in accordance with the provisions of the existing laws, and that scholars further deepen the thematic approached, with the aim of changing the reality of public places in the City of Belém.